Upaya Meningkatkan Kreativitas Anak dengan Memanfaatkan Limbah Daun Kering Menjadi Sebuah Karya Seni Kolase - Zakiyyah Zakiyyah; Putri Amelia; Imam Hadiwibowo (IAIN Syekh Nurjati Cirebon, 2023)
EFFORTS TO INCREASE CHILDREN'S CREATIVITY BY UTILIZING DRY LEAF WASTE TO BECOME A COLLAGE ARTWORK. Indonesia is a tropical country that only has two seasons, namely Dry and Rainy. During the dry season the weather was hot and many of the trees whose leaves had fallen were blown by the wind so that they were scattered everywhere. And the lack of public awareness of this dry leaf wasted which can interfere with the scenery and roads. The Collaborative KKM program is implemented to contribute to the community in processing and utilizing dried leaf waste into a valuable work of art, in this case carried out in the village of Ciledug Kulon, Ciledug District, Cirebon City. The methode used in this Collaborative KKM activity is collage, which is a two-dimensional work of art where the way of making it is by attaching dry leaves using glue to form an image of work of art. This KKM activity produces products from the results of utilizing dried leaf waste in the form of works of art that can be used as wall decorations